MAHASISWI BERCADAR DALAM INTERAKSI SOSIALNYA DI KAMPUS UNIVERSITAS RIAU - Rahma Apri Nursani; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in the campus of Universitas Riau Simpang Baru, Panam. The purpose of this research is to know and analyze what is the background of Student’s veil and how the social interaction of student veiled in Riau University Campus. The focus of the research is the interaction of student niqab with the environment that many corners and have not received the existence of individualis who use the campus then what are the factors of internal and external underlying the use of veils among the students of the sampling technique purposive sampling set the number of research subjects as many as 6 people. The author uses qualitative descriptive methods and data instruments are observations, interviews and documentation.Of research conducted, the authors found that there are several reasons behind the use of niqab among female students that is understanding in religion, changing themselves to be a good muslimah, the willingness in oneself to use the veil, advice from parents and the influence of friends and the environment. The student interaction is covered with the environment that now a days many emerging negative assumptions with the veil, the author claims that the interaction with the faculty lecturers or lecturers during the teaching and learning activities in the calssroom did not accept niqab students to enter the class on the grounds do not recognize the face of female students and afraid of later masculine female student other people who replace the position of masculine female student in the class, staff campus many of them do not recognize who the person behind the niqab, but the intercation between the two runs just fine as usual, friends of a group or friends women who have long intercted with female student niqab always have difficulty to recognize his own friend who used the niqab, difficulty recognizing someone who is not visible face, interction student niqab will limit themselves and set the distance and rarely there is interaction with Non-muslim friens or just a greeting.Keywords : Interaction, Female student, Niqab, Pekanbaru